Beyond donors and giving: examining alumni citizenship behaviors for university success - Shaari, Hasnizam; Md Salleh, Salniza; Perumal, Selvan; Zainol, Fakrul Anwar (2018)
Loyal alumni are a key ingredient for overall universities success. In highly competitive and advancement of higher education market, it is paramount important not only to understand how relationship marketing promote students' satisfaction but to extend the boundary of knowledge on how later (as alumni) they could enhanced overall university success. As alumni donors and giving behaviors had received considerable attention in the past studies, this study attempts to propose alumni supportive behaviors that goes beyond donors and giving and seeks to examine how and why they behave towards their alma mater. As such, this study proposed that alumni supportive behavior could be conceptualized as alumni citizenship behaviors (ACBs). Grounded with Social Exchange Theory and Relationship Marketing, this study seeks to examine how both institutional and individual predictors could arouse ACBs. More importantly, this study hopes to profile and develop a multidimensionality of ACBs conception that goes beyond donors and giving and examine the effect of alumni community engagement on the proposed relationship. The results using PLS-SEM 3.0 based of 193 alumni from eight public universities in Malaysia revealed that university reputation and university engagement significantly influenced alumni citizenship behaviors. Personal & social responsibility influenced university engagement. Beside, university engagement partially mediate the relationship between personal & social responsibility and alumni citizenship behaviors. This study extend the body of knowledge that alumni citizenship behaviors is best explained by multidimensional construct i.e. donor behavior, alumni loyalty and alumni support. Contribution, limitation as well as future research direction also highlighted at the end of the report.